Effect of cadmium on transmembrane Na+ and K+ transport systems in human erythrocytes. Issue 6 (June 1991) - Lijnen, P; Staessen, J; Fagard, R; Amery, A
Abstract : The effects of cadmium (Cd2+) on Na+, K(+)-ATPase in disrupted human erythrocyte membranes and on various transmembrane Na+ and K+ transport systems in intact erythrocyte suspensions were studied. Cadmium2+ inhibited the erythrocyte Na+, K(+)-ATPase enzyme with a 50% inhibition at a Cd2+ concentration of 6.25 microM. The Cd2+ inhibition in the human erythrocyte was non-competitive with respect to Na+, K+, and ATP. Cadmium2+ exerted no acute effect, however, on the Na+, K(+)-ATPase pump activity as measured by the ouabain sensitive 86Rb uptake or Na+ efflux in intact red blood cells. Cadmium2+ also inhibited the Ca2+ dependent K+ channels in human red blood cells, whereas it had no effect on Na+, K+ cotransport, Na+, Li+ countertransport, anion carrier, and the number of active Na+ pump units. The data indicate that in human erythrocytes under acute conditions Cd2+ exerts an inhibitory effect on Na+, K(+)-ATPase enzyme in disrupted erythrocytes and the Ca2+ stimulated K+ efflux in intact red blood cells without affecting the Na+ pump, Na+, K+ cotransport, and Na+, Li+ countertransport activity.